2021
DOI: 10.3390/plants10061224
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Biologically Active Properties of Medicinal Plant Cotinus coggygria

Abstract: The results of the studies have shown that to obtain an extract of a complex of biologically active substances of Cotinus coggygria, ethyl alcohol (mass fraction of alcohol 70%) with a hydromodule of 1:5 should be used, and the extraction should be carried out for 60 min at a temperature of 60 °C. The investigated plant extracts with the complex of bioactive substances from the Cotinus coggygria leaves and flowers are safe from the point of view of the content of heavy metals, pesticides, aflatoxin B1, radionu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 28 publications
0
19
2
Order By: Relevance
“…Hassan et al [23] showed that C. coggygria is characterized by low oxalic acid content. Thus, the oxalic acid content in Cotinus coggygria [8] in our studies is 3.74 times lower than its content in D. maculata [7].…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…Hassan et al [23] showed that C. coggygria is characterized by low oxalic acid content. Thus, the oxalic acid content in Cotinus coggygria [8] in our studies is 3.74 times lower than its content in D. maculata [7].…”
Section: Discussioncontrasting
confidence: 69%
“…It was shown that samples of BAS complex extracts isolated from the studied medicinal plants from different regions (Table 9) had an inhibitory effect on the E. coli test strain. Lysis zone was from 13.6 to 16.5 mm, from 15.2 to 17.0 mm, and from 15.1 to 17.0 mm for C. coggygria [8], D. maculata [7], and P. chlorantha, respectively. Platanthera chlorantha samples from the Eastern Baltics exhibited high antibacterial activity against S. aureus (lysis zone 18.0 mm).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations